2005
DOI: 10.1902/jop.2005.76.6.991
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Root Planing and Systemic Metronidazole Administration Improve Clinical and Microbiological Outcomes in a Two‐Step Treatment Procedure

Abstract: The present results show that the extent of root planing has a distinct influence on treatment outcomes. Patients treated with the highest instrumentation frequency showed the best long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
(43 reference statements)
3
33
1
4
Order By: Relevance
“…They have been studied both as adjunctive therapies with scaling and root planing and as stand-alone chemotherapies. [4][5][6] However, they have little long term efficacy in the treatment of periodontitis in addition to side effects and development of bacterial resistance due to systemic administration of these agents. 7,8 Therefore, local delivery of antimicrobial agents has been investigated as a possible approach for treatment of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been studied both as adjunctive therapies with scaling and root planing and as stand-alone chemotherapies. [4][5][6] However, they have little long term efficacy in the treatment of periodontitis in addition to side effects and development of bacterial resistance due to systemic administration of these agents. 7,8 Therefore, local delivery of antimicrobial agents has been investigated as a possible approach for treatment of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…10 Treatment of periodontits requires a high concentration of antimicrobials to be available in the periodontal pocket as an adjunctive therapy with scaling and root planing. 5,11 Using a sustained local antimicrobial delivery system will be more beneficial regarding the ease of application and selectively targeting a limited number of diseased sites that were unresponsive to conventional therapy. 9,12 Many researchers have demonstrated that sustained delivery of antimicrobial agents can be effective in reducing signs of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] To treat such specific, destructive infections, adjunctive antibiotic therapy 25 has been used, albeit with varying results. [26][27][28][29][30][31][32][33] The purpose of the present study is to test the hypothesis that there is no difference in the clinical outcomes in terms of the patient mean clinical attachment level (CAL), the patient mean probing depth (PD), and absence of PDs ‡5 mm among groups of patients treated with conventional, SRP performed over 2 to 3 weeks, or same-day FDIS, with or without adjunctive metronidazole. The present report presents the clinical results at 3 and 12 months after treatment.…”
mentioning
confidence: 99%
“…PrtC might play a role in the initiation and development of peri-odontitis by working in combination with other factors produced by P gingivalis or host cells, including P gingivalis LPS or MMP [31,32] , since the relationships between PrtC levels and these clinical parameters seem to be rather complicated. It was notable that the PrtC-positive subgingival samples were reduced from 90.8% to 66.8%, and the PrtC level decreased remarkably in different AL sites or in the ≤6 mm PD pockets (P<0.05) after treatment, which might be explained by the fact that mechanical debridement will significantly decrease the number of P gingivalis and other putative periodontal pathogens [32,33] . However, the A 490 value of PrtC in the BOP-positive samples and in the sites with >6 mm PD changed insignificantly (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, the A 490 value of PrtC in the BOP-positive samples and in the sites with >6 mm PD changed insignificantly (P>0.05). Previous studies have indicated that deep pockets and furcations are most likely inadequately instrumented [34] and microorganisms, including P gingivalis residing in biofilms left in such locations, correlated with BOP and greater pocket depths [35] , which may require surgical intervention [32] . Our results also contributed to the above viewpoints.…”
Section: Discussionmentioning
confidence: 99%